Fabrication of defective graphene oxide for efficient hydrogen production and enhanced 4-nitro-phenol reduction - Raza, Waseem; Ahmad, Khursheed; Kim, Haekyoung (Nanotechnology, 2021)
Hydrogen has been considered as one of the most promising alternative energy source to solve the future energy demands due to its high energy capacity and emission-free character. The generation of hydrogen from non-fossil sources is necessary for the sustainable development of human life on this planet. The hydrolysis of sodium borohydride can quickly produce a large amount of hydrogen in situ and on-demand in the presence of the catalyst, which can be used as an alternative energy source. So, it is crucial to fabricate the highly efficient, robust, and economical catalyst for the production of hydrogen via hydrolysis of sodium borohydride. Herein, a facile and efficient approach for the synthesis of metal-functionalized reduced graphene oxide for the production of hydrogen at room temperature was used. Moreover, the synthesized catalyst has also been tested in the field of environmental catalysis for the reduction of toxic 4-nitrophenol to valuable 4-aminophenol in the presence of sodium borohydride. The enhanced activity of prepared metal-functionalized reduced graphene oxide is ascribed to a strong affinity between Fe-N (X) and reduced graphene oxide which facilitates electron transfer as well as synergistic effect. Overall, this work presents a crucial procedure for green chemistry reactions when a carbonaceous material is selected as a catalyst.
CRIS-Team WoS Importer:2021-09-24